2012
DOI: 10.2489/jswc.67.6.474
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of drainage water management on subsurface drain flow, nitrate concentration, and nitrate loads in Indiana

Abstract: Drainage water management is a conservation practice that has the potential to reduce drainage outflow and nitrate (NO 3 ) loss from agricultural fields while maintaining or improving crop yields. The goal of this study was to quantify the impact of drainage water management on drain flow, NO 3 concentration, and NO 3 load from subsurface drainage on two farms in Indiana. Paired field studies were conducted following the paired watershed statistical approach modified to accommodate autocorrelation. Annual NO 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 24 publications
1
24
0
Order By: Relevance
“…In some cases (Jaynes 2012;Helmers et al 2012), the demonstration sites were established consistent with a field research approach, where the effect of DWM could be compared to conventional drainage in well-instrumented, field-scale, replicated plots. In others (Cooke and Verma 2012;Ghane et al 2012;Adeuya et al 2012), paired DWM and conventionally drained sites were established on farmer-operated, production-scale fields, located on a range of soils and conditions across a wide region of a state. There are advantages and disadvantages to both approaches.…”
Section: Five-state Drainage Watermentioning
confidence: 99%
“…In some cases (Jaynes 2012;Helmers et al 2012), the demonstration sites were established consistent with a field research approach, where the effect of DWM could be compared to conventional drainage in well-instrumented, field-scale, replicated plots. In others (Cooke and Verma 2012;Ghane et al 2012;Adeuya et al 2012), paired DWM and conventionally drained sites were established on farmer-operated, production-scale fields, located on a range of soils and conditions across a wide region of a state. There are advantages and disadvantages to both approaches.…”
Section: Five-state Drainage Watermentioning
confidence: 99%
“…This limitation was highlighted in a long-term simulation across the Midwest region, in which a controlled-outlet system was found to be most effective in southern areas of the Midwest, such as Missouri, Illinois, Indiana, and Ohio (reductions of 35.8 to 46.3 kg N ha ), which was mostly attributed to differences in the timing of precipitation and drainage (Thorp et al, 2008). In west-central Indiana, DRAINMOD modeling by Ale et al (2010) showed that the majority (>80%) of N loss reduction with DWM occurred during the non-growing season (November through April), which is also typically when the majority of annual precipitation and drainage occurs (Adeuya et al, 2012). However, in regions similar to southeast Iowa, the timing of the majority of annual precipitation (50%) and drainage (70%) (April, May, and June) generally coincides with the release of drainage water through the control structure to allow for spring field activities (Helmers et al, 2005;Thorp et al, 2008).…”
Section: Long-term Simulationsmentioning
confidence: 99%
“…Unlike conventional drainage systems that remove excess water to the design drain depth whenever it occurs, controlled drainage stores water by increasing the retention time of water in the soil profile thereby reducing annual drainage volumes. Controlled drainage has been shown to be effective in reducing the outflow of water and nitrate-nitrogen (nitrate-N) from drainage systems (Adeuya et al, 2012;Cooke and Verma, 2012;Helmers et al, 2012;Jaynes, 2012 …”
Section: Controlled Drainagementioning
confidence: 99%